Aplicação da análise fatorial em cidades do Vale do Paraíba considerando os objetivos do milênio - Santos, Herivelto Tiago Marcondes dos [UNESP] (2015)
The urban planning of cities has been an important element in the choices or application possibilities of the Millennium Development Goals proposed by the UN in 2000. In the metropolitan region of the Paraiba Valley and Northern Coast, living conditions and the ways of choice for development, in the course of the 20th century, besides the high degree of urbanization of cities, are key to socioeconomic characteristics of the region. Led by typically urban economic characteristics of polo cities and its neighborhoods, that region was constructed by a land occupation with similar difficulties to the beginning of the occupation of other cities like Sao Paulo and Rio de Janeiro, with predominant economic activities associated with trade, services and industry. This work aims at presenting the opportunities that are offered for this region, in order to achieve the Millennium Development Goals, in order to better target the decision-making and the resources available to the cities. For this, we used the multivariate analysis known as Factor Analysis, which suggests identifying factors through the extraction of principal components that best correlate to Millennium Development Goals and energy use. As part of the conclusions we have that the electric intensity of the cities is a vector for the urban planning of cities toward better living conditions of their populations, and the need for greater encouragement of partnerships between cities so as sanitation needs take effect for better living conditions beyond the care with the aware use of water and energy